Case report: Treatment of parkinsonism secondary to ciltacabtagene autoleucel using a combination dopaminergic regimen - Aliakbar, Raya; Manouvakhova, Olga; Wong, Cindy; Htut, Myo; Pulst-Korenberg, Johannes; Janakiram, Murali; Rosenzweig, Michael; Goldsmith, Scott R.; Mason, Xenos L. (Frontiers in Immunology, 2024)
We report on a patient with Ciltacabtagene autoleucel-induced movement and neurocognitive toxicity, which was refractory to immunosuppression but responsive to combination dopaminergic therapy (carbidopa/levodopa, ropinirole, amantadine). Response was seen upon both initial treatment and rechallenge after unintended withdrawal. This is the first report of successful symptomatic treatment of this well-described neurotoxic syndrome.